The role of parents in school (Journal of Parents and Teachers, 2026)
It reflects on the role that parents play in school, criticising the model that views parents as mere 'customers' of the education service.It argues that education is a task shared between the family and the school, in which parents should actively participate. It also proposes a series of attitudes to achieve active collaboration in the school.
Keywords: Participation, family, school, and collaboration.